Elevated prevalence of malnutrition and malaria among school-aged children and adolescents in war-ravaged South Sudan. (17th November 2015) - Charchuk, Rhianna; Houston, Stan; Hawkes, Michael T.
Abstract : Emerging as a sovereign state from decades of civil war, the Republic of South Sudan now faces poverty, a lack of health care infrastructure, a high burden of infectious diseases and a widespread food insecurity. School-aged children and youth, in particular, represent a high-risk demographic for malnutrition and infectious diseases. We screened 109 school-aged children and youth for nutritional status and malaria antigenaemia in Akuak Rak, South Sudan, and found a large proportion of underweight (77/109 = 73%) and prevalent malaria (44/109 = 40%). There was no significant association between malnutrition and malaria. This study represents one of the few published reports on child and youth nutritional status and malaria prevalence in South Sudan since its independence. The implementation of nutrition and malaria screening combined with evidence-based interventions in schools could help target this high burden vulnerable group.